Knowledge and experience of Kazakhstan athletes in anti-doping and the impact of past educational intervention - Galiya Zhumabayeva; Gulnara Kapanova; Denis Vinnikov; Maira Bakasheva; Venera Abdulla; Andrej Grjibovski (BMC, 2022)
Abstract Background Although Kazakhstan National Anti-Doping Organization (KazNADO) exists since 2013, but little is yet known about anti-doping (AD) knowledge of Kazakhstan athletes. The aim of this study was to assess the AD education knowledge level and experience among Kazakhstan athletes, as well as the impact of any past AD educational program on them. Methods Altogether, 590 athletes (the median was age 17 years (interquartile range 8)), representing various sports, participated in the web-based study and completed the questionnaire, which consisted of socio-demographic part and ALPHA test. We assessed the association of any past AD education and experience with anti-doping knowledge using adjusted regression models. Results A total of 54.6% participants underwent doping control and 82,7% of athletes received AD education at least once. More than 300 participants (50.8%) provided correct answers for 10 questions. Age and years in sports (competition duration) were significantly associated with the ALPHA scores of athletes. Athletes who received AD education more than once in the past had significantly higher ALPHA scores than non-AD educated athletes in most questions. Conclusion AD education was associated with AD knowledge. Further research is needed to identify the adherence to anti-doping knowledge.